Meningkatkan Rasa Cinta Tanah Air Melalui Pemanfaatan Media Cerita Wayang Kulit : Meningkatkan Rasa Cinta Tanah Air Melalui Pemanfaatan Media Cerita Wayang Kulit - Sujana, I Putu Windu Mertha; Pradana, Aldy Panji; Utami, Anak Agung Istri Dewi Adhi; Pertiwi, Ni Ketut Santya Isana; Putra, I Putu Hendy Jayadi (Jurnal IKA, 2025)
Wayang kulit is one of the local wisdom of the community that contains good values ​​to develop the character of the younger generation. This study aims to increase the love of the homeland by utilizing the story of the Petruk Dadi Ratu wayang kulit as a learning medium and increasing students' learning motivation with more efficient delivery. The approach used in this study is descriptive qualitative, taking the research location at SMP Santo Paulus Singaraja, the research subjects were determined through snowball sampling techniques, data collection using observation techniques, interviews, documentation, and questionnaires, and the data analysis technique using interactive model data analysis consisting of data reduction, data presentation, and drawing conclusions. The results obtained from this study are (1) implementing an attitude of love for the homeland through flag ceremonies, singing mandatory songs, commemorating national days, displaying the national symbol, and mid-semester breaks, (2) the values ​​contained in the Petruk Dadi Ratu shadow puppet story include two indicators, namely, preserving the arts and culture of the homeland, and instilling nationalism of unity and togetherness, (3) The results of the attitudes shown by students after watching the Petruk Dadi Ratu shadow puppet story are that there is an increase in love for the homeland, although not very significant, this is based on habits that students have done previously.